Liquid-Filled Hollow Core Bragg Fiber Sensors Using Different Bandgaps for High-Refractive-Index Sensing - Liang Shang; Sujuan Feng (IEEE Photonics Journal)
Liquid-filled hollow core Bragg fibers (HCBFs) provide an excellent platform for refractive index (RI) sensing. The capacity for high-RI sensing based on higher order bandgaps of an HCBF is explored for higher sensitivity. We numerically compare the performances of an As2S3/PEI-based HCBF RI sensor using first-order and second-order photonic bandgaps (PBGs) for high-RI sensing. The influences of material dispersion and structural parameters on the sensing performance for both PBGs are investigated comparatively. Similar to the first-order PBG, the modification of the bandgap structure induced by material dispersion can also help to improve the linearity of an RI sensor using the second-order PBG of a conventional HCBF. For first-order and second-order PBGs including material dispersion, both a reduction in confinement loss and an improvement in sensitivity can be achieved by increasing the cladding period. In contrast, the influence of the period number on the sensitivity for a first-order PBG is contrary to that for a second-order PBG, which may be attributed to their different reflection characteristics. Furthermore, the comparative results show that a liquid-filled defect HCBF RI sensor using the second-order PBG can achieve high sensitivity and high linearity by optimizing the structural parameters of the defect layer. The proposed RI sensor would have great potential in the real-time measurement of high-RI liquid analytes.